PENERAPAN KRIPTOGRAFI VIGENERE CIPHER PADA KEAMANAN DATA PESAN TEKS BERBASIS WEBSITE - Suwinda Aulansari; Diah Sawitri; Ali Ikhwan (Jurnal Informatika Teknologi dan Sains, 2022)
Security is an urgent component of an information system. However, this is still very rarely realized by the owner or manager of the information system. That results in information being exchanged or compromised by parties who are not supposed to receive the message. Therefore, a data security system is needed so that information doesn’t crash into the wrong hands. To control data security, you can use cryptography, one of which is the vigenere cipher algorithm. This research uses a literature study research method sourced from various journals and experiments by designing and implementing systems. The final result of the application implementing the vigenere cipher algorithm is expected to help maintain the security of information.